(3GdYfhGf aj GdbQGAGJ GdSHYs - (3ESeGYjd Hf Nda Hf SYjO GdCfUGQj, GdnqSnQobrSWj , CHh GdWGgQ,J (B455 (3g` s ((3YHO Gdbhi Hf YHO Gddg Hf GHQGgje Hf eMeO GdGfeGWi GdSYOi s)
(3ChdgG (B:s
(3bGd GdTjN GHh WGgQ GSeGYjd GdMeO ddg GdPi GfTCfG HbOQJg hgOGfG ddESdGe haWQJg CeG HYO aEfi OGcQ ai gPG GdcJGH Ef TGA Gddg eG ENJda ajg GdbQGA GdSHYI GdeTghQhf ef CFeI GdGeUGQ s
(3BNQgG (B:s
(3jfJgi HHGH PcQ GdJcHjQ s
(3HBNQg ELGRI ef GdcGJH hgh ef GdYdeGA ai GdbQGAGJ ddTjN YKeGf Hf Ydi Hf jMji GdeYQha HGHf GdNTGH SfI (B634(3g` hUhQI ELGRI CNQi SfI (B653(3g` dYKeGf Hf Ydi Hf jMji GdeYQha HGHf HfJ CHj SYOs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B268s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1176s
Keywords: (3GdbQGAGJ hGdJLhjOs